The Effects of Contextual Clues Within A Picture of Road Signs on Students’ Vocabulary Mastery - Herli Salim; Suryadi Suryadi; Fajar Erlangga (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This study aims to determine the effects of contextual clue within picture of road sign on students’ vocabulary mastery. The design of the research was a true experimental study with Pretest-Posttest Group Design. Learning outcome data are obtained through pretest and posttest activities. The samples were 80 students randomly taken by adjusting to the condition and aim of the research. There was a significant difference from the results of the experimental class posttest and control class this was evidenced by the Fo value. Fo value was 5.491 and Sig was 0.024 <0.05. It means that there was a difference in an effect of contextual clue within picture of road sign on students’ vocabulary mastery.